Observations on the origin of Phaseolus polyanthus Greenman - Schmit, Véronique; Debouck, Daniel G. (Springer, 1991)
Total seed protein variability in a sample of 163 entries of year-bean (Phaseolus polyanthus), including wild, feral and cultivated forms of the whole range of distribution in Latin America was studied using 1-dimensional SDS/PAGE and 2-dimensional IEF-SDS/PAGE. Ten different patterns were observed in this crop. Eight of these are found in the Mesoamerican materials, the other two of those in the northern Andes. The highest diversity is found in the wild ancestral forms present in central Guatemala with six patterns. The b pattern predominant in all Mesoamerican cultivated materials is also present at low frequency in Colombia. The k pattern, predominant in the northern Andes, is present in Costa Rica. These results together with information on indigenous names for the crop suggest that there is a single gene pool domesticated from a wild ancestor still present in Guatemala, and distributed afterwards to the northern Andes, but with a clinal genetic drift from Mesoamerica to the Andean region. (AS)